Utility of Centrifugation-Controlled Convective (C3) Flow for Rapid On-chip ELISA - Espulgar, Wilfred (Sci Rep, 2019)
Miniaturizing the enzyme-linked immunosorbent assay (ELISA) protocols in microfluidics is sought after by researchers for a rapid, high throughput screening, on-site diagnosis, and ease in operation for detection and quantification of biomarkers. Herein, we report the use of the centrifugation-controlled convective (C3) flow as an alternative method in fluid flow control in a ring-structured channel for enhanced on-chip ELISA. A system that consists of a rotating heater stage and a microfluidic disk chip has been developed and demonstrated to detect IgA. The ring-structured channel was partially filled with microbeads (250 µm in diameter) carrying the capture antibodies and the analyte solution was driven by thermal convection flow (50 µL/min) to promote the reaction. The remaining part of the circular channel without microbeads served as the observation area to measure the absorbance value of the labeled protein. Currently, the system is capable of conducting four reactions in parallel and can be performed within 30 min at 300 G. A detection limit of 6.16 ng/mL using 24 µL of target sample (IgA) was observed. By simply changing the capture antibodies, the system is expected to be versatile for other immunoassays.